The Evolution of Mosque Architecture and the Distinctive Characteristics of Its Structural Elements - Mohamed Tribak; Mekki Klaina (Darul Yasin Al Sys, 2025)
This study examines the evolution of mosque architecture within Islamic civilization by analyzing its structural components, functional roles, and symbolic significance. It highlights the mosque not only as a sacred space for worship but also as a central institution in the social and urban fabric of Islamic society. Despite undergoing architectural transformations across centuries, the mosque has retained its spiritual essence and distinctive identity. Through a descriptive and comparative approach, the study investigates defining architectural elements, including domes, minarets, miḥrābs, minbars, and ornamental motifs using selected examples from the Islamic East, the Maghrib, and al-Andalus. Central to the inquiry is how mosque architecture has maintained its foundation in Islamic religious principles while engaging with diverse cultural and artistic traditions. The findings suggest that mosque architecture embodies a dynamic and adaptive tradition: deeply rooted in Islamic values yet responsive to historical change and regional context. This reflects the broader character of Islamic civilization, open to external influences without relinquishing its unique identity.